Revitalizing São Cristóvão: Integrating Industry, Commerce, and Community for a Sustainable Urban Future - Vidya Gotmare (International Journal of Urban Design and Development, 2026)
This paper introduces a comprehensive framework for the sustainable regeneration of São Cristóvão, a historically industrial district in Rio de Janeiro, South America, which presently demonstrates significant urban deterioration, socio-economic instability, and increasing environmental hazards. Through an interdisciplinary methodology integrating spatial analysis, ethnographic profiling, environmental assessment, and stakeholder engagement, the study develops a phased master plan aimed at transforming the neighborhood into a resilient, inclusive, and economically diverse urban environment. The proposed strategy emphasizes the systematic integration of industrial activities, commercial functions, mixed-income housing, and cultural infrastructure to enhance spatial continuity and support balanced urban development. The proposed framework is structured around three core, interdependent interventions. First, a prototype eco-industrial cluster utilizes circular economy principles and industrial ecology to enhance resource efficiency, reduce waste flows, and strengthen small- and medium-scale manufacturing networks. Second, the revitalization of the canal system into a connected blue-green infrastructure corridor mitigates chronic flooding while improving ecological performance, active mobility, and public realm quality. Third, the introduction of affordable mixed-use housing co-located with light industry advances social equity by supporting climate-responsive, policy-aligned living and working environments. The master plan further incorporates mixed-use zoning, resource-efficient land allocation, pedestrian- and transit-oriented mobility systems, and climate-responsive architectural strategies. Key components include flood-adaptive land use frameworks, ecological restoration of waterways, sponge-city systems, distributed renewable energy generation, and low-carbon mobility networks consistent with Rio de Janeiro’s Net Zero 2050 agenda. The São Cristóvão proposed eco-industrial zones (EIZ) concept aims to achieve regulatory clarity, long-term stewardship, and meaningful community participation through a phased implementation timeframe (2025-2050) and multi-stakeholder governance. The study provides a transportable model of regenerative post-industrial urbanism that can be applied to Global South contexts experiencing similar transitions.
Keywords: Rio de Janeiro; São Cristóvão; Urban resilience; circular economy; climate-responsive design; environmental justice; inclusive urban development; industrial districts; industrial ecology; mixed-use development; net zero 2050; post-industrial landscapes; sponge-city infrastructure; urban regeneration; waterfront redevelopment